2022
DOI: 10.3390/microorganisms10010124
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic In Vitro Antimicrobial Activity of Triton X-100 and Metformin against Enterococcus faecalis in Normal and High-Glucose Conditions

Abstract: The prevention and treatment of oral diseases is more difficult in diabetic patients with poorly controlled blood glucose levels. This study aims to explore an effective, low-cytotoxicity medication for root canal treatment in diabetic patients. The antibacterial effect of the combination of Triton X-100 (TX-100) and metformin (Met) on Enterococcus faecalis (E. faecalis) was evaluated by determining the minimum inhibitory concentration (MIC), minimum bactericidal concentration required to kill 99% bacteria (MB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 53 publications
0
6
0
Order By: Relevance
“…He and ark. [17] investigated synergies between metformin and Triton X-100 in the antibacterial effects of E. faecalis isolates. When metformin and Triton X-100 were combined, they were found to be well below the MIC values detected when used alone.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…He and ark. [17] investigated synergies between metformin and Triton X-100 in the antibacterial effects of E. faecalis isolates. When metformin and Triton X-100 were combined, they were found to be well below the MIC values detected when used alone.…”
Section: Discussionmentioning
confidence: 99%
“…Another study investigated the cytotoxic effect of metformin on cells, but no significant cytotoxin effect was observed. Another study, in which the synergy between metformin and Triton X-100 was investigated, investigated the cytotoxicity of metformine, and found no significant cytotoxin in the control group [17]. Another study using Ag+ and metformin on E. faecalis isolates found no significant difference in cell proliferation from the control group to the metformine-treated group [15].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present study, the effects of metformin on immune regulation and antibacterial activity were investigated in detail in a rat model of H. pylori infection. Metformin has potential activity against H. pylori, but there is ample evidence of its synergistic effect with conventional antibiotics against Gram-positive and Gram-negative bacteria [5,9,[26][27][28]. Previously, Courtois et al reported that 10 mg/mouse/day of metformin had antibacterial activity 9].…”
Section: Discussionmentioning
confidence: 99%
“…In fact, by downregulating the expression of stress genes and CcpA, the combination of TX-100 and metformin hampered the stress response and glycolytic capacity of E. faecalis , thereby decreasing their viability and proliferation and diminishing their pathogenicity and drug resistance. Furthermore, they ascertained the antibiofilm activity of this association against E. faecalis in a dentin biofilm model [ 86 ].…”
Section: Other Compoundsmentioning
confidence: 99%